Cardiogenic Shock Complicating ST-Segment Elevation Myocardial Infarction: An 18-Year Analysis of Temporal Trends, Epidemiology, Management, and Outcomes. Issue 3 (3rd March 2022) - Vallabhajosyula, Saraschandra; Dewaswala, Nakeya; Sundaragiri, Pranathi R.; Bhopalwala, Huzefa M.; Cheungpasitporn, Wisit; Doshi, Rajkumar; Miller, P. Elliott; Bell, Malcolm R.; Singh, Mandeep
ABSTRACT: Background: There are limited data on the temporal trends, incidence, and outcomes of ST-segment-elevation myocardial infarction-cardiogenic shock (STEMI-CS). Methods: Adult (>18 years) STEMI-CS admissions were identified using the National Inpatient Sample (2000–2017) and classified by tertiles of admission year (2000–2005, 2006–2011, 2012–2017). Outcomes of interest included temporal trends, acute organ failure, cardiac procedures, in-hospital mortality, hospitalization costs, and length of stay. Results: In ∼4.3 million STEMI admissions, CS was noted in 368, 820 (8.5%). STEMI-CS incidence increased from 5.8% in 2000 to 13.0% in 2017 (patient and hospital characteristics adjusted odds ratio [aOR] 2.45 [95% confidence interval CI 2.40–2.49]; P < 0.001). Multiorgan failure increased from 55.5% (2000–2005) to 74.3% (2012–2017). Between 2000 and 2017, coronary angiography and percutaneous coronary intervention use increased from 58.8% to 80.1% and 38.6% to 70.6%, whereas coronary artery bypass grafting decreased from 14.9% to 10.4% (all P < 0.001). Over the study period, the use of intra-aortic balloon pump (40.6%–37.6%) decreased, and both percutaneous left ventricular assist devices (0%–12.9%) and extra-corporeal membrane oxygenation (0%–2.8%) increased (all P < 0.001). In hospital mortality decreased from 49.6% in 2000 to 32.7% in 2017 (aOR 0.29 [95% CI 0.28–0.31]; P < 0.001). During the 18-year period, hospital lengths of stay decreased, hospitalization costs increased and use of durable left ventricular assist device /cardiac transplantation remained stable ( P > 0.05). Conclusions: In the United States, incidence of CS in STEMI has increased 2.5-fold between 2000 and 2017, while in-hospital mortality has decreased during the study period. Use of coronary angiography and PCI increased during the study period.